Gambaran Etika Digital terhadap Perilaku Akademik Mahasiswa di Era Kecerdasan Buatan/Artifical Intelligence (AI) (Studi Kasus STAI KHARISMA) - Kun Nurachadijat; Yulia SanicaPopy; Sita Nurhomsah; Rizki Utari (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study aims to describe the overview of digital ethics and academic behavior of STAI KHARISMA students in the era of artificial intelligence. The research employed a descriptive quantitative approach with a survey method. The sample consisted of 50 students selected through purposive sampling. The instrument used was a questionnaire with 16 statement items using a Likert scale of 1-5. Data analysis was conducted descriptively by calculating frequencies, percentages, and mean scores. The results showed that the level of students' digital ethics was high with a mean score of 33.6 out of 40. The digital communication ethics indicator obtained the highest percentage (92%), while the digital honesty indicator obtained the lowest percentage (72%). The level of students' academic behavior was also high with a mean score of 32.2 out of 40. The academic discipline indicator obtained the highest percentage (86%), while the academic integrity indicator obtained the lowest percentage (70%). This study concludes that STAI KHARISMA students already have good digital ethics and academic behavior, but there is still a need for improvement in the aspects of digital honesty and academic integrity.